2021
DOI: 10.1007/s13730-021-00641-7
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy in a patient with pulmonary tuberculosis infection and lung adenocarcinoma: a case report

Abstract: We report a case of membranous nephropathy (MN) in a patient with tuberculosis infection and lung adenocarcinoma. A 50-year-old Filipino woman underwent a renal biopsy for the evaluation of proteinuria and hematuria. Immunofluorescence analysis revealed positive staining of IgG in the glomerular basement membrane and mesangial matrices, while electron microscopy demonstrated the presence of sub-epithelial deposits, suggesting MN. To screen for secondary causes of MN, we conducted a computed tomography (CT) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Previous investigations have demonstrated that remission of MN can be observed following effective antitumor treatment in patients with MN with concomitant malignancy. 8,10,15,16,18,19,21 Our study supports these findings. Specifically, in case 4, case 8, case 10, and case 14, patients who did not receive immunosuppressive therapy, achieved PR/CR of MN after surgical removal of the tumor or chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous investigations have demonstrated that remission of MN can be observed following effective antitumor treatment in patients with MN with concomitant malignancy. 8,10,15,16,18,19,21 Our study supports these findings. Specifically, in case 4, case 8, case 10, and case 14, patients who did not receive immunosuppressive therapy, achieved PR/CR of MN after surgical removal of the tumor or chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…We retrieved and summarized the literature on MN patients with concomitant malignancy from 1990 to the present, screening 17 articles encompassing a total of 21 patients in whom MN-specific antigen staining was performed on both renal and tumor tissues simultaneously (Figure 3). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Among these patients, 71.4% (15/21) were male, with a median age of 61.0 years (56. 3, 72.8).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clinically, cancer-related nephropathy is on the rise, but the pathological types are atypical and the etiology is unclear 3,4 . Although several reports mention improvement in symptoms of nephrotic syndrome in patients with MN after aggressive tumor treatment [5][6][7] , the evidence that directly reveals this relationship is still limited, controversial, and speculative 8 . It has been reported that the processes of MN and malignancy often develop in parallel, with tumor antigens or tumor-reactive antibodies found within glomerular immune deposits, supporting an association between the two diseases 9 .…”
mentioning
confidence: 99%
“…Twenty-three patients had positive antinuclear autoantibodies. Infectious agents, a known trigger of MN, 5 , 6 , 7 , 8 , 9 were not identified (including hepatitis B virus, hepatitis C virus, HIV, malaria, leprosy, or tuberculosis).…”
Section: Resultsmentioning
confidence: 99%